DAYAK LAWANGAN BALIAN BAWO IN CENTRAL DUSUN, EAST BARITO, CENTRAL KALIMANTAN - Liber Sigai, Ervanta Restulita; Kumbara, A.A Ngurah Anom; Cika, I Wayan; Arsana, I Gusti Ketut Gde (E-Journal of Cultural Studies, 2016)
Globalization with all its implications has affected the life of Dayak Lawangan living in Central Dusun. Modernization has caused balian bawo to be getting scarce. The number of the speakers of balian bawo is decreasing, and it seems that no young generation is interested in it, although its existence still functions in various aspects of the Dayak Lawangan community’s life. In addition, the young generation is less interested in becoming balian bawo. This will affect the process of the regeneration of balian bawo. The result of the present study shows that the practice of balian waho is obtained through the myth and process of becoming balian bawo. This causes balian bawo to be the central position in the practice of balian bawo ritual. Balian waho plays an important role in the healing and purifying processes. It functions to prevent both manifest and latent misfortunes. It is the socio-cultural supporting life regulation for Dayak Lawangan. It is made up of religiosity, culture conservation, social life, and aesthetics. The formal education, the discontinuity of the internationalization process in families, the low income earned by those who work as balian bawo, their risky responsibility, the spiritual and physical abilities they need, and their religious and psychological ideologies have caused those who are interested in becoming balian bawo to decrease. The impacts are that the dimensions of time and magic formula as part of the ritual practice will change. In addition, the ideological struggle for the ritual practice of balian bawo, and the change in the population of balian waho will also result from the scarcity of the population of balian waho. As well, the social and solidarity ties will be getting weaker and the funds needed for the ritual will be high enough.